Replication protein A in nonearly ovarian adenocarcinomas: Correlation with MCM-2, MCM-5, Ki-67 index and prognostic significance - G Levidou; Ventouri, K.; Nonni, A.; Gakiopoulou, H; Bamias, A.; Sotiropoulou, M.; Papaspirou, I.; Dimopoulos, M.A.; Patsouris, E.; P Korkolopoulou (International Journal of Gynecological Pathology, 2012)
Replication protein A (RPA) is an ssDNA-binding protein required for the initiation of DNA replication and the stabilization of ssDNA. Collaboration with several molecules, that is, the MCM2-7 complex, has been suggested to be imperative for its multifaceted role. In this study, we investigated the immunohistochemical expression of the RPA2 subunit in correlation with the MCM-2 and MCM-5 and Ki67 index, and assessed its prognostic significance in 76 patients with nonearly ovarian adenocarcinomas, the majority of whom had a serous histotype. RPA2 protein expression was observed in all cases, whereas the staining intensity varied from weak to strong. RPA2 expression was correlated with the tumor stage in the entire cohort and in serous tumors (P=0.0053 in both relationships). Moreover, RPA2 immunoexpression was positively correlated with MCM-2 (P=0.0001) and MCM-5 (P<0.0001) expression, but was unrelated to the Ki67 index (P>0.10). In multivariate survival analysis, RPA2 expression emerged as an independent predictor of adverse outcome (P<0.0001) along with tumor histologic grade. RPA2 remained an independent predictor of survival (P=0.002) even after adjustment for MCM-2 and MCM-5 expression and when analysis was restricted to serous carcinomas (P=0.004). Our results further support the interrelation of RPA2 protein with MCM-2 and MCM-5 in OCs. Moreover, RPA2 protein may play an important role in ovarian tumorigenesis, and may serve as a useful independent molecular marker for stratifying patients with OC in terms of prognosis. © 2012 International Society of Gynecological Pathologists.
Keywords: Immunohistochemistry; Ovarian adenocarcinoma; RPA